ONOMATOPOEIA: LIFE EXPERIENCES OF POETS ON EXPRESSING AGGRESSION - Avila, Roy Paul; Fuentes, Jezel Mae; Borbon, Jennifer G; Garcia, Georgette S; Ramos, Cake Aerolyn (PEOPLE: International Journal of Social Sciences, 2018)
People engaged in writing and performing poetry as a way of expressing their emotions is a rising phenomenon. The study aimed to know the life experiences of poets in coping with aggression through poetry writing. As well as to know if there is a significant data that will prove the existence of the aggression that motivates poets to write. The study utilized the qualitative design it’s an inquiry process of understanding based on particular distinct methodological traditions on request that investigate a social or human problem, under the Qualitative design the researchers used the Case Study method The respondents of the study were two female and two male poetry writers, 18 years old and above and who writes poetry for at least 3 years, and has an average deviation / average score from the Buss-Perry Aggression test. The researchers conducted the study on different cities in the National Capital Region. The researchers were able to come up with the following themes; (1) Personal experiences (2) Social experiences (3) Coping mechanisms. These themes shows the lived experiences of the poets in dealing with aggression by using poetry as a mechanism in coping up with the different aspects of life that significantly contributes to their aggression. We recommend for future researchers to utilize different approaches and expand the scope of this research.